2016
DOI: 10.1038/srep25232
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing proteins with transverse ionic transport in nanochannels

Abstract: De novo protein sequencing is essential for understanding cellular processes that govern the function of living organisms and all sequence modifications that occur after a protein has been constructed from its corresponding DNA code. By obtaining the order of the amino acids that compose a given protein one can then determine both its secondary and tertiary structures through structure prediction, which is used to create models for protein aggregation diseases such as Alzheimer’s Disease. Here, we propose a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…This could, however, be overcome by chemically attaching a polypeptide to the N-terminus of proteins. Other approaches have been proposed, but lack experimental proof [100][101][102][103] . Sampath proposed the use of a double pore system in which two nanopores are placed in series 100 .…”
Section: Protein Sequencing Using Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation
“…This could, however, be overcome by chemically attaching a polypeptide to the N-terminus of proteins. Other approaches have been proposed, but lack experimental proof [100][101][102][103] . Sampath proposed the use of a double pore system in which two nanopores are placed in series 100 .…”
Section: Protein Sequencing Using Nanoporesmentioning
confidence: 99%
“…As the polypeptide transverses the first pore, it is cleaved by an exopeptidase, and the amino acids released by the enzyme are then analysed with a second nanopore. DiVentra and colleagues proposed the use of perpendicular nanochannels in which a protein is stretched in the longitudinal direction, while ionic current is recorded transversally 101 . Aksimentiev and colleagues proposed the use of graphene to control polypeptide translocation.…”
Section: Protein Sequencing Using Nanoporesmentioning
confidence: 99%
“…Many obstacles need to be overcome in implementation, such as the rapid translocation through the upstream nanopore, which can be solved by a series of methods discussed above, and whether the statistical distribution of different amino acids' signal through downstream can reach enough accuracy for distinguishing. On this point, Boynton et al simulated the use of vertical nanochannels to stretch the protein in the vertical direction while recording the ion current in the horizontal direction [120]. They found that the distributions of ionic currents for each of the 20 amino acids were statistically different, which providing a possible approach for de novo protein sequencing.…”
Section: Protein Sequencing Using Solid-state Nanoporesmentioning
confidence: 99%
“…Such methods are beginning to show promise and are set to compete with the more established methods mentioned above [10]. In contrast, nanopore-based protein sequencing is still in its infancy; a variety of methods, some in theory [11][12][13][14], others in practice [15][16][17][18], are known. Recently it has been reported that 13 of the 20 standard amino acids (obtained by finely grinding a protein) riding on a carrier molecule translocating through an aerolysin nanopore have long enough dwell times in the pore to allow discrimination among them based on the volume that each of them excludes in the pore [19].…”
Section: Introductionmentioning
confidence: 99%